The Effect of Regret Experienced in Investment Decision: an Experimental Study - Elisa Daniati Edison; Hesty Aisyah (International Journal of Asian Business and Management, 2023)
This study explore the psychology of bias experienced stock investors when making an investment decision. The research method used is by an experimental design 2x5 factorial between subject.  Researchers conducted manipulation on two different treatment condition (good and regretful experience) to the stock investors which refers to the theory of regret aversion bias. The experiment using a web stock simulation with participans as many as 70 students who were divided according to their risk aversion. Other research instrumen use a questionnaire using a measurement scale of 1-5. The experiment results show that experienced regret affect subsequentthe next investment choices of  investors. There was no interaction between experience of regret with investors' risk aversion